Determination of fenticonazole enantiomers by LC-ESI-MS/MS and its application to pharmacokinetic studies in female rats - Feng, Zhenbin; Zou, Qiaogen; Tan, Xiaoheng; Che, Wenjun; Zhang, Zunjian (Arzneimittelforschung, 2011)
A simple, rapid, and specific high-performance liquid Chromatograph coupled with a tandem mass spectrometry method has been developed and validated for the determination of fenticonazole (CAS 72479-26-6) enantiomers in rat plasma. Simple protein precipitation by acetonitrile was utilized for extracting analytes from the plasma samples. Chromatography separation was performed on a C18 analytical column (150 mm × 2.0 mm, 5 µm) with a mobile phase consisting of methanol-10 mM aqueous ammonium acetate (adjusted to pH 3.5 with acetic acid) (90:10, v/v) at a flow rate of 0.2 ml/min. Detection was carried out on a triple quadrupole mass spectrometer equipped with electrospray ionization (ESI) source, and operated in multiple-reaction monitoring (MRM) mode. The calibration curves were linear over the range 0.5 – 200 ng/ml (r > 0.99). The relative recoveries of R-(−)-fenticonazole and its enantiomer were better than 85%. The intra- and inter-day precisions (R.S.D.%) and deviations of the assay accuracies were less than 10%. This newly developed and validated method was successfully applied to pharmacokinetic studies after administration at a single dose of 20 mg/kg R-(−)-fenticonazole nitrate and its enantiomer to female rats per vagina. The Cmax value of S-(+)-fenticonazole was greater than that of R-(−)-fenticonazole by 1.36-fold, whereas, the t1/2 ß and MRT values of R-(−)-fenticonazole were longer than those of its enantiomer by 1.95- and 1.24-fold. The results indicated that S-(+)-fenticonazole was faster in absorption and elimination in female rat. But, the Tmax and AUC(0–12) values for each of fenticonazole enantiomers were not significantly different.
Keywords: Antifungal agent; Enantiomer; Fenticonazole; Pharmacokinetics; Liquid chromatography/tandem mass spectrometry (LC-MS/MS)